The Influence Of Culture, Individual Differences And Time Pressure On Negotiation Styles Of Iranian And Malaysian Business Negotiators - Rad, Navid Fatehi (2015)

(untitled)
Kajian ini meneliti pengaruh budaya dan perbezaan individu dari segi personaliti, kecerdasan emosi dan jantina ke atas gaya perundingan (bersaing, berkolaborasi, berkompromi, mengelakkan dan menampung) kedua-dua para perunding perniagaan dari Iran dan Malaysia.Kajian ini juga meneliti kesan kesederhanaan tekanan masa ke atas hubungan antara budaya dan gaya rundingan para perunding perniagaan dari Malaysia dan Iran.Teknik persampelan bertujuan bukan rawak telah digunakan untuk mengumpul data melalui soal selidik yang dihasilkan dari literatur dan kajian yang berkaitan. Data dianalisis dengan menggunakan perisian SPSS. Hasil kajian menunjukkan bahawa dimensi budaya (kolektivisme, kelakian, jarak kuasa dan pengelakan ketidaktentuan) mempunyai pengaruh yang besar ke atas gaya perundingan kedua-dua perunding perniagaan Iran dan Malaysia. Di samping itu, berdasarkan hasil analisis data (analisis regresi berganda), gaya bekerjasama, bertolak ansur dan bertimbang rasa telah diketengahkan sebagai gaya perundingan yang paling digemari oleh perunding perniagaan Iran (mengikut nilai mutlak pekali β). Bersaing dan mengelakkan gaya telah diketengahkan sebagai gaya perundingan yang paling digemari oleh perunding perniagaan Malaysia (mengikut nilai mutlak pekali β). The present study examined the influence of culture and individual differences in terms of personality, emotional intelligence and gender on negotiation styles (competing, collaborating, compromising, avoiding and accommodating) of both Iranian and Malaysian business negotiators. This research also investigated the moderating effect of time pressure on the relationship between culture and negotiation styles of business negotiators from Malaysia and Iran. Non-random purposive sampling technique was applied to collect data through survey questionnaire developed from related literature and studies. The data were analyzed by using SPSS software. Findings indicated that dimensions of culture (collectivism, masculinity, power distance and uncertainty avoidance) had significant influences on negotiation styles of both Iranian and Malaysian business negotiators. In addition, based on the results of data analysis (multiple regression analysis) collaborating, compromising and accommodating styles were highlighted as the most preferred negotiation styles of Iranian business negotiators (according to the absolute value of β coefficient). Competing and avoiding styles were highlighted as the most preferred negotiation styles of Malaysian business negotiators (according to the absolute value of β coefficient).